Upaya Pendekatan Kedokteran Keluarga pada Wanita 62 Tahun dengan Hiperkolesterolemia di Aceh Utara - Noviana Zara; Azman Bripo (Quantum Wellness : Jurnal Ilmu Kesehatan, 2025)
Mrs. Km visited the Integrated Health Post (Posbindu) in Alue Keureunyai Village with complaints of throbbing neck pain that had occurred intermittently over the past two weeks and worsened in the last day. The pain intensified after consuming fatty or coconut milk-based foods and improved with rest or cholesterol-lowering medication. She also experienced a persistent, heavy, throbbing headache for two weeks and ongoing fatigue for the past three weeks, despite minimal physical activity. These symptoms led to reduced motivation in daily activities. Physical examination showed: BP 160/100 mmHg, HR 88 bpm, RR 20 breaths/min, T 36.8°C. Laboratory results revealed a total cholesterol level of 250 mg/dL. Data were gathered through auto-anamnesis, physical and laboratory examinations, home visits, completion of the family folder, and patient documentation. Assessment was based on holistic diagnosis at the initial, ongoing, and final stages of the visit, using both qualitative and quantitative approaches. Interventions included education on the causes of hypercholesterolemia, the importance of taking medication regularly, and awareness of complications due to high cholesterol levels.